To evaluate the role of microvascular procedure in diabetic foot using diabetic foot score - Gopal Singh; Amit Agarwal (Asian Journal of Medical Sciences, 2025)
Background: Diabetic foot ulcers (DFUs) pose significant medical and socioeconomic challenges, being a leading cause of non-traumatic lower-limb amputations. Microvascular reconstructive procedures have emerged as vital interventions for limb salvage, but their role in achieving optimal outcomes in DFU management remains underexplored, particularly in northern India. Aims and Objectives: This study aimed to evaluate the efficacy of microvascular procedures in DFU management using a diabetic foot scoring system. Objectives included protocol development for surgical management, standardizing practices, assessing procedure success rates, and analyzing post-operative outcomes such as ambulation time, complications, and hospital stay duration. Materials and Methods: A prospective observational study was conducted at a tertiary care center, including 40 diabetic patients with non-healing ulcers refractory to conservative management. Patients were stratified into low, moderate, and high-risk categories using diabetic foot scores based on parameters such as ankle-brachial pressure index, necrotizing fasciitis, and osteomyelitis. Free flaps were selected based on individual risk profiles. Outcomes were assessed in terms of wound healing, ambulation, and complication rates. Results: Microvascular procedures demonstrated a 100% healing rate, with 18 patients (45%) achieving healing through primary intervention and 22 (55%) requiring additional procedures. Mean healing and ambulation times were 40.55±7.63 days and 60.75±10.17 days, respectively. High-risk patients (9; 22.5%) experienced prolonged hospital stays and higher rates of complications. Conclusion: Microvascular procedures are effective for DFU management, especially in high-risk patients. The developed protocol ensured standardized care and optimized outcomes, underscoring the importance of risk stratification and multidisciplinary approaches in limb salvage.